Analisa Kinerja Struktur Beton Bertulang Pasca Kebakaran - Latip, Abdullah (INTEK: Jurnal Penelitian, 2016)
This Paper aims to analyze the performance level of Pasar Butung post-fire on December 15, 2010. The fire was centered on the 1st and 2nd floor. Data retrieval include visual observation, carbonation test, concrete hammer test, concrete core test and tensile test of steel reinforcement that was held on January, 2011. All data that was taken will use to analyze the structure. Observations indicate that the temperature of the fire around 400oC. Beams and columns on floors 1 and 2 had cracks and the quality of concrete fell 62% from 21.15 MPa to 14 MPa at the outer cross-section. While the floor plates 2 and 3 having a width of cracks and residual concrete quality is only 11.57 MPa. Pushover analysis (static lateral load) is a nonlinear static analysis that can provide detailed information about the collapse behavior of structures against earthquake loads, while the performance point is the magnitude of the maximum displacement of the structure during an earthquake plan. Results of 3D nonlinear static pushover analysis on the structure of Pasar Butung shows that performance point is achieved when the base reaction V reach 484.97 tons with displacement of 0.021 m (2.1 cm) at step 3. Results of analysis showed that the performance of the structure is still within the limits of Life Safety.